Monitoring Indoor Air Quality in Classrooms Using Low-Cost Sensors: Does the Perception of Teachers Match Reality? - Nuno Canha; Carolina Correia; Sergio Mendez; Carla A. Gamelas; Miguel Felizardo (Atmosphere)
This study intended to understand whether teachers’ perceptions of indoor air quality (IAQ) during classes aligned with the real levels of air pollutants and comfort parameters. For this purpose, an IAQ monitoring survey based on low-cost sensors using a multi-parameter approach was carried out in nine classrooms (a total of 171 monitored classes) in a Portuguese school. In each monitored class, the perception of IAQ reported by the teacher was assessed using a scale from 1 (very bad IAQ) to 10 (very good IAQ). Several exceedances regarding national legislation were found, with temperature being the parameter with a higher percentage of exceedance in all the studied classrooms (46%), followed by PM10 (32%), and then CO2 (27%). Temperature was found to be the only environmental parameter that was significantly associated with lower IAQ perception reported by the teachers, highlighting that typical pollutants such as CO2 (which can be identified as stuffy air) did not contribute to the teachers’ perceptions.